An inverse problem to simulate the transport of chloride in concrete by time–space fractional diffusion model. Issue 12 (2nd December 2021) - Feng, Chenqing; Si, Xinhui; Li, Botong; Cao, Limei; Zhu, Jing
Abstract : In this paper, we proposed a fractional diffusion model to simulate the movement of chloride in concrete. In such complex porous structure some of the free chlorides, which are affected by the surrounding heterogeneous physical environment, will be bounded physically and chemically. Furthermore, experiments reveal that the interesting heavy-tailed phenomena appear in diffusion process. The time and spatial fractional derivatives are introduced to explain the anomalous diffusion and the dependence of medium properties. The numerical research shows that present model could better fit the experimental data and the diffusion of chloride in concrete is time-dependent and space-dependent.